A Study on Sustainable Competitive Advantage by Managing Service Quality at a Multi Speciality Corporate Hospital, Chennai - Dharani Priya, G.; Jabarethina, G. (Prabandhan: Indian Journal of Management, 2016)
Organizations are faced with a lot of changes in the current scenario. Sustainable competitive advantage allows the maintenance and enhancement of markets and maintains the competitive position of an organization. It ensures the long-term growth of the organization and results in stronger brand, greater pricing power and operational efficiencies, increases customer loyalty and enhances the ability to attract, retain, and motivate employees. A hospital is much more complex than other manufacturing organizations, since it undertakes medical and health responsibilities that deal with the lives of people. The whole chain of service delivery characteristically involves numerous communications between patients, health care providers, and other employees. The success of private hospitals depends on patients’ perceptions on the quality of products and services provided by the service personnel in hospitals. Service quality becomes increasingly important to measure how well the services delivered meet patients’ expectations. This study was based on the factors of Porter’s model, that is, cost, technology, people, capability, and resources ; and the SERVQUAL dimensions, that is, reliability, assurance, responsiveness, tangibles, and empathy to achieve excellence in service quality. The excellence in service quality automatically enhances the path to sustainable competitive advantage and thus results in stronger brand ; greater pricing power and operational efficiencies;increases customer loyalty and enhances the ability to attract, retain, and motivate employees.